Dually Modified Cellulose as a Non-Viral Vector for the Delivery and Uptake of HDAC3 siRNA - Juliana Hülsmann; Henry Lindemann; Jamila Wegener; Marie Kühne; Maren Godmann; Andreas Koschella; Sina M. Coldewey; Thomas Heinze; Thorsten Heinzel (Pharmaceutics, 2023)
RNA interference can be applied to different target genes for treating a variety of diseases, but an appropriate delivery system is necessary to ensure the transport of intact siRNAs to the site of action. In this study, cellulose was dually modified to create a non-viral vector for HDAC3 short interfering RNA (siRNA) transfer into cells. A guanidinium group introduced positive charges into the cellulose to allow complexation of negatively charged genetic material. Furthermore, a biotin group fixed by a polyethylene glycol (PEG) spacer was attached to the polymer to allow, if required, the binding of targeting ligands. The resulting polyplexes with HDAC3 siRNA had a size below 200 nm and a positive zeta potential of up to 15 mV. For N/P ratio 2 and higher, the polymer could efficiently complex siRNA. Nanoparticles, based on this dually modified derivative, revealed a low cytotoxicity. Only minor effects on the endothelial barrier integrity and a transfection efficiency in HEK293 cells higher than Lipofectamine 2000TM were found. The uptake and release of the polyplexes were confirmed by immunofluorescence imaging. This study indicates that the modified biopolymer is an auspicious biocompatible non-viral vector with biotin as a promising moiety.